1997
DOI: 10.1002/(sici)1097-0045(19970701)32:2<77::aid-pros1>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active immunization against luteinizing hormone‐releasing hormone on the androgen‐sensitive Dunning R3327‐PAP and androgen‐independent Dunning R3327‐AT2.1 prostate cancer sublines

Abstract: BACKGROUND. The objective of this study was to determine the effect of active immunization against LHRH on the growth characteristics and histology of subcutaneously implanted tumors of the androgen-sensitive Dunning R3327-PAP and androgen-independent R3327-AT2.1 rat prostate adenocarcinoma sublines. RESULTS. We herein demonstrate that 1) active immunization with an LHRH-diphtheria toxoid-conjugate (LHRH-DT) leads to the downregulation of gonadotropins and testosterone and consequently the atrophy of testoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Dunning tumor clones adopted to rats were used for this purpose. The growth ofthe androgen-dependent cancer cells was markedly inhibited in the LHRH-vaccinated rats (63). The inhibition was dne to reduction of the mitotic index and not due to enhanced apoptosis.…”
Section: Carcinoma Ofthe Prostatementioning
confidence: 93%
“…Dunning tumor clones adopted to rats were used for this purpose. The growth ofthe androgen-dependent cancer cells was markedly inhibited in the LHRH-vaccinated rats (63). The inhibition was dne to reduction of the mitotic index and not due to enhanced apoptosis.…”
Section: Carcinoma Ofthe Prostatementioning
confidence: 93%
“…Inference was drawn that at this stage the cancer had become androgen-independent. Studies in rats implanted with androgen-sensitive Dunning R3327-PAP and androgen-independent Dunning R3327-AT2.1 sublines have shown that LHRH vaccine suppresses effectively the growth of androgen-sensitive tumors and has partial but not full effect on androgenindependent Dunning tumor cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…Active immunization against LHRH was tested in rats [78]. Its effect on the growth characteristics and histology of subcutaneously implanted androgen-sensitive and androgenindependent tumors was studied.…”
Section: Cancer Vaccines Targeting the Hormone Lhrh/gnrhmentioning
confidence: 99%